PENGEMBANGAN FRAMEWORK UNTUK MENENTUKAN INTERVAL AGE BASED INSPECTION YANG OPTIMUM DENGAN APLIKASI RANTAI MARKOV - , MONANDA WANDITA RINI, Hari Agung Yuniarto, S.T., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of activities in preventive maintenance is inspection. The objective of inspection is to obtain information related to the condition of machine or component. If the frequency of inspection is higher, the information of machineâs condition is also much more so maintenance action can be done effectively. But, inspection spends inspection cost. If inspection cost is expensive, short interval of inspection can rise the total inspection cost. On the other hand, long interval of inspection can rise the replacement cost. Thus, optimum interval of inspection needs to be determined. There are two type of inspection which are fix interval inspection and age based inspection. In the age based inspection, inspection is done at long interval when early age, and then interval become shorter as time goes by. This research develops a framework to determine optimum interval of age based inspection by application of markov chain. The test of framework was done at case study in PT. XYZ. Framework of age based inspection in this research consists of three phase are equipment analysis, markov analysis, and decision making process. Total process in this framework is ten processes. The first until fiftth process included to one phase which is equipment analysis as phase I. The sixth until eighth process included to one phase which is markov analysis as phase II. The ninth until tenth process included to one phase which is decision making process. As phase III. Framework of age based inspection is integrated with phase, input, process, output, and method/software. Framework of age based inspection was tested at study case in PT. XYZ. By following the all process in the framework, optimum interval of age based inspection for critical component can be obtained. The first inspection can be done at the interval 50-80 hour. The second inspection can be done at the interval 30-50 hour. The third inspection can be done at the interval 30-50 hour. The fourth inspection can be done at the interval 30-50 hour. Based on comparison analysis, the proposed interval inspection gives lower average cost rate and total cost rate than interval inspection based on companyâs policy, but has consideration of component reliability